2019
DOI: 10.7556/jaoa.2019.125
|View full text |Cite
|
Sign up to set email alerts
|

An Osteopathic Physician's Approach to the Esports Athlete

Abstract: Esports is gaining acceptance in the world of professional, collegiate, and high school athletics. However, there is a lack of information for osteopathic physicians about the health concerns and appropriate treatment of esports athletes. Because of the sedentary nature of the sport and accompanying poor posture, esports athletes are likely to have musculoskeletal injuries of the neck, back, and upper extremities. Additionally, these athletes may have metabolic disturbances resulting from light-emitting diode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 39 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…Approximately 78% ( n = 225) of USA and 74% ( n = 128) of Australian esports players did not meet PA guidelines, whereas 40% and 30.4% of the general population from these respective countries did. As esports is sedentary in nature, the overall lack of PA being undertaken by esports players could leave large numbers of players at future risk of serious health problems, such as back, neck and wrist injuries [ 17 ], as well as chronic diseases associated with sedentary behaviour [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 78% ( n = 225) of USA and 74% ( n = 128) of Australian esports players did not meet PA guidelines, whereas 40% and 30.4% of the general population from these respective countries did. As esports is sedentary in nature, the overall lack of PA being undertaken by esports players could leave large numbers of players at future risk of serious health problems, such as back, neck and wrist injuries [ 17 ], as well as chronic diseases associated with sedentary behaviour [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Partly supporting our hypothesis, results showed that players in the top 10% of player in-game ranks participated in PA more days per week compared to those in the bottom 90% of esports players. Previous research investigating PA and esports players found that the motivation to participate in PA is most frequently for general health benefits, with a smaller percentage of players being physically active with performance enhancement in mind [ 16 , 17 , 18 ]. Although the present study is cross-sectional in nature, it appears that those players with a higher in-game rank are more likely to be active on more days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pain interfered with daily activities, but it usually still might be controlled. 8 These study findings proved that the longer the duration of playing online games, the higher possibility of getting neck disabilities.…”
Section: Discussionmentioning
confidence: 70%
“…Using the discourses of health and applying these discourses to the construction of G Fuel's brand and image makes sense considering that energy drinks have somewhat of a stigma for containing caffeine and taurine, as well as being associated with various physical and mental health problems (Seifert et al 2011;Richards & Smith 2016). There have been concerns about these ingredients and their effects on children and adolescents, who comprise a large audience to the influencers advertising G Fuel (Zwibel et al 2019;Stout 2015). To counter these concerns, G Fuel's website frames the product in opposition to other energy drinks, performing a "search for novelty or innovation" persona (Marshall, Moore & Barbour 2020, p.65).…”
Section: G Fuel's Websitementioning
confidence: 99%